How do we best engage young people in decision-making about their health? A scoping review of deliberative priority setting methods - Daniella Watson; Mimi Mhlaba; Gontse Molelekeng; Thulani Andrew Chauke; Sara Correia Simao; Sarah Jenner; Lisa J. Ware; Mary Barker (BMC, 2023)
Abstract Introduction International organisations have called to increase young people's involvement in healthcare and health policy development. We currently lack effective methods for facilitating meaningful engagement by young people in health-related decision-making. The purpose of this scoping review is to identify deliberative priority setting methods and explore the effectiveness of these in engaging young people in healthcare and health policy decision-making. Methods Seven databases were searched systematically, using MeSH and free text terms, for articles published in English before July 2021 that described the use of deliberative priority setting methods for health decision-making with young people. All titles, abstracts and full-text papers were screened by a team of six independent reviewers between them. Data extraction followed the Centre for Reviews and Dissemination guidelines. The results are presented as a narrative synthesis, structured around four components for evaluating deliberative processes: 1) representation and inclusion of diverse participants, 2) the way the process is run including levels and timing of participant engagement, 3) the quality of the information provided to participants and 4) resulting outcomes and decisions. Findings The search yielded 9 reviews and 21 studies. The more engaging deliberative priority setting tools involved young people-led committees, mixed methods for identifying and prioritising issues and digital data collection and communication tools. Long-term and frequent contact with young people to build trust underpinned the success of some of the tools, as did offering incentives for taking part and skills development using creative methods. The review also suggests that successful priority setting processes with young people involve consideration of power dynamics, since young people's decisions are likely to be made together with family members, health professionals and academics. Discussion Young people's engagement in decision-making about their health is best achieved through investing time in building strong relationships and ensuring young people are appropriately rewarded for their time and contribution. If young people are to be instrumental in improving their health and architects of their own futures, decision-making processes need to respect young people's autonomy and agency. Our review suggests that methods of power-sharing with young people do exist but that they have yet to be adopted by organisations and global institutions setting global health policy.